NCOG-68. COMPARING COGNITIVE PROFILES OF PERSONS WITH BRAIN AND NON-BRAIN METASTATIC CANCER. (9th November 2020) - Willhelm, Gabrielle; Del Bene, Victor; Aita, Stephen; Gammon, Meredith; Gerstenecker, Adam; Fiveash, John; Marotta, Dario; Triebel, Kristen
Abstract: OBJECTIVE: Cognitive impairment in primary cancer and brain metastatic (BM) cancer has been well-documented. However, to date, there are no neuropsychological studies comparing the cognitive profiles of people with BM and non-brain metastatic cancer (NBM). The present study addressed this gap in the literature by comparing the cognitive profiles of participants with BM and NBM. METHOD: The study sample consisted of 61 BM, 40 NBM, and 37 healthy control (HC) participants. All participants completed the same neuropsychological battery, including tests of processing speed, attention, working memory, expressive language, auditory-verbal memory, and executive functioning. RESULTS: Both clinical groups showed reduced processing speed, verbal learning/memory, and executive functions. BM participants performed below HC participants across all neuropsychological tests, while NBM participants performed below control participants on tests of processing speed and executive functioning. The clinical groups differed in semantic verbal fluency (NBM > BM). Fifty-seven percent of BM participants had ≥ 3 impaired scores (i.e., ≤ 5 th percentile), and 25% of NBM participants had the same level of cognitive impairment. CONCLUSION: Over half of BM participants were cognitively impaired on at least three neuropsychological tests, and 25% of NBM participants also demonstrated this same level of cognitive impairment. In the BM group, the elevated rate of cognitive dysfunction is likely due to the greater neurologic disease burden posed by brain metastases, while in the NBM group, the cognitive deficits are possibly due to systemic illness and treatment effects.